HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP DALAM PENERAPAN PROTOKOL KESEHATAN DI KARANG TARUNA DUSUN MALANGJIWAN - Reni Puspita Sari; Uji Utami (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2021)
COVID-19 has been declared a world pandemic by WHO. The knowledge that the community should have will be very influential in preventing the transmission of Covid-19, becauseknowledge is one of the domains of behavior besides attitudes and actions or practices(Bloom, 1908 in Notoatmodjo, 2014). With the incessant provision of information related toCovid-19 and health protocols by the government either directly or through mass media orsocial media, it is hoped that it can change people’s attitudes and behavior to be aware andalways comply with health protocols required by the government. The purpose of this study wasto analyze the relationship between knowledge and attitudes in the implementation of healthprotocols at Karangtaruna in Malangjiwan Hamlet. The research method used was analytic observational with cross sectional approach. The research was conducted at Karangtaruna Dusun Malangjiwan in February 2021. The population of this study were all teenagers whocame to the Karangtaruna meeting as many as 47 people. Data on knowledge and attitudesin the respondents’ health protocol presentation were collected using a questionnaire andanalyzed using the Spearman test. The results showed that the knowledge of respondents inthe health protocol presentation was mostly in the medium category, namely as many as 29respondents (62%). Most of the respondents’ attitudes in the health protocol presentation werein the negative category, namely as many as 29 respondents (62%). The Spearman test of therespondents’ knowledge and attitudes showed p value = 0.001 (p 0.05). From these results itcan be concluded that there is a relationship between the level of knowledge and attitudes in theapplication of health protocols during the Covid-19 pandemic.Keywords: Knowledge, Attitude, Application of Health ProtocolsABSTRAKCOVID-19 telah dinyatakan sebagai pandemi dunia oleh WHO. Pengetahuan yang seharusnya dimiliki masyarakat akan sangat berpengaruh dalam tindakan pencegahan penularan Covid-19,karena pengetahuan merupakan salah satu ranah perilaku selain sikap dan tindakan atau praktik(Bloom, 1908 dalam Notoatmodjo, 2014). Dengan gencarnya pemberian informasi terkait dengan Covid-19 dan protocol kesehatan oleh pemerintah baik secara langsung ataupun melalui media masa atau social media diharapkan dapat merubah sikap dan perilaku masyarakat untuk sadar danselalu mematuhi protocol kesehatan yang diwajibkan oleh pemerintah. Tujuan dari penelitian iniadalah untuk menganalisis hubungan antara pengetahuan dan sikap dalam penerapan protokolkesehatan pada Karangtaruna di Dusun Malangjiwan. Metode penelitian yang digunakan adalahobservasional analitik dengan pendekatan cross sectional. Penelitian dilakukan di KarangtarunaDusun Malangjiwan pada bulan Februari 2021. Populasi dari penelitian ini adalah semua remajayang datang pada pertemuan Karangtaruna sebanyak 47 orang. Data pengetahuan dan sikapdalam penerapan protokol kesehatan responden dikumpulkan menggunakan kuesioner dan 1dianalisis dengan uji spearman. Hasil penelitian menunjukkan bahwa pengetahuan respondendalam penerapan protokol kesehatan sebagian besar dalam kategori sedang yaitu sebanyak 29responden (62%). sikap responden dalam penerapan protokol kesehatan sebagian besar dalamkategori negatif yaitu sebanyak 29 responden (62%). Uji spearman terhadap pengetahuandan sikap responden menunjukkan nilai p value = 0,001 (p0,05). Dari hasil tersebut dapatdisimpulkan bahwa ada hubungan antara tingkat pengetahuan dengan sikap dalam penerapanprotokol kesehatan selama masa pandemi Covid-19Kata Kunci: Pengetahuan, Sikap, penerapan protokol kesehatan